2017
DOI: 10.1039/c6ra25610d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles with fluorescence and affinity for DNA sensing and nucleus staining

Abstract: The fluorescence magnetic nanoparticles offer versatile platforms for nucleus imaging and DNA adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…It can be caused by the DNA binding to bare iron oxide nanoparticles and precipitation of the DNA-SPION complexes by the external magnetic field. Previously the possibility of electrostatic complexes formation between positively charged nanoparticles and DNA was shown in [14][15][16]. The experiments at higher relative DNA concentrations demonstrate qualitatively similar results (Fig.…”
Section: Methodssupporting
confidence: 83%
“…It can be caused by the DNA binding to bare iron oxide nanoparticles and precipitation of the DNA-SPION complexes by the external magnetic field. Previously the possibility of electrostatic complexes formation between positively charged nanoparticles and DNA was shown in [14][15][16]. The experiments at higher relative DNA concentrations demonstrate qualitatively similar results (Fig.…”
Section: Methodssupporting
confidence: 83%
“…A GFP-fused carbohydrate-binding module (type 3a family [ 41 ], GFP–CBM3A) was selected to detect cellulose in biological tissues and to track its localization in histological slides. The GFP–CBM adsorption on BNC and BCNC was compared and the obtained data fitted to the Langmuir adsorption model [ 43 , 44 ]. Figure 3 shows the adsorption isotherms of GFP–CBM onto BNC and BCNC and the respective parameters of the Langmuir isotherm.…”
Section: Resultsmentioning
confidence: 99%
“…A non-linear regression analysis was used to calculate the parameters of the Langmuir adsorption isotherm [ 43 , 44 ]: where GFP–CBM Bound is the amount of adsorbed protein per unit mass of cellulose (mg/mg), GFP–CBM Free is the protein concentration (mg/mL) in the liquid phase at the adsorption equilibrium, GFP–CBM Max is the maximum amount of adsorbed protein per unit mass of cellulose (mg/mg), and K a is the Langmuir constant (mL/mg). Three independent assays were performed, each of them in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Hoechst 33342 has been mostly used for ow cytometry [32][33][34] . On the other hand, H33258 staining has been predominantly used in uorescence microscopy 18,19,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some papers reported that the nucleus of apoptotic cells can exhibit enhanced uorescence after Hoechst binding [15][16][17] . Therefore, Hoechst probes have been frequently used for nucleus staining in uorescence microscopy and ow cytometry [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%